2024
DOI: 10.1038/s41592-024-02208-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of 20 amino acids and discrimination of pathologically relevant peptides with functionalized nanopore

Ming Zhang,
Chao Tang,
Zichun Wang
et al.

Abstract: Precise identification and quantification of amino acids is crucial for many biological applications. Here we report a copper(II)-functionalized Mycobacterium smegmatis porin A (MspA) nanopore with the N91H substitution, which enables direct identification of all 20 proteinogenic amino acids when combined with a machine-learning algorithm. The validation accuracy reaches 99.1%, with 30.9% signal recovery. The feasibility of ultrasensitive quantification of amino acids was also demonstrated at the nanomolar ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…28 Another exciting option is nanopore technology, which was first commercialized for DNA and RNA sequencing, and is now emerging as a promising tool for peptide sequencing. Recent achievements include the detection of all 20 proteinogenic amino acids, real-time analyses of post-translational modifications (PTMs), 29 and peptide sequencing by sequentially cleaving amino acids from the Cterminus. 30 Although this technology currently struggles with large-scale sequencing under complex conditions, it has undoubtedly holds promise as a rising star.…”
Section: A Need For High Throughput Proteomicsmentioning
confidence: 99%
“…28 Another exciting option is nanopore technology, which was first commercialized for DNA and RNA sequencing, and is now emerging as a promising tool for peptide sequencing. Recent achievements include the detection of all 20 proteinogenic amino acids, real-time analyses of post-translational modifications (PTMs), 29 and peptide sequencing by sequentially cleaving amino acids from the Cterminus. 30 Although this technology currently struggles with large-scale sequencing under complex conditions, it has undoubtedly holds promise as a rising star.…”
Section: A Need For High Throughput Proteomicsmentioning
confidence: 99%
“…Step 2. In the sorted list count the number of duplicates down the string and output copy count for protein Complexity of mixture sequencing and quantification 1) In Procedure AssembleSequencesFromConjugateSequenceMatrix there are M 20 distinct paths of length 20 from the first column to the 20 th column of CSM[M] [20]. In the worst case all of them may be examined, so the worst-case behavior is O(M 20 ).…”
Section: Procedures Quantifysamplefrommproteinsequencesmentioning
confidence: 99%
“…For a recent review of nanopore-based methods, see [12]. Specific studies can be found in [13][14][15][16][17][18][19][20].…”
Section: Protein Sequencing In the Bulk And At The Single Molecule Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The other emerging technology from genomics is nanopore sequencing, in which the passing of a linearised amino acid chain through a protein-based nanopore induces specific measurable electrical current changes depending on each particular amino acid [ 214 , 215 ]. There is recent evidence to suggest that PTM can also be identified and localised with this technology [ 216 , 217 ].…”
Section: Recognising and Addressing Critical Issuesmentioning
confidence: 99%